2021
DOI: 10.48550/arxiv.2112.01153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homes' law in holographic superconductor with linear-$T$ resistivity

Hyun-Sik Jeong,
Keun-Young Kim

Abstract: Homes' law, ρ s = C σ DC T c , is a universal relation of superconductors between the superfluid density ρ s at zero temperature, the critical temperature T c and the electric DC conductivity σ DC at T c . Experimentally, Homes' law is observed in high T c superconductors with linear-T resistivity in the normal phase, giving a material independent universal constant C. By using holographic models related to the Gubser-Rocha model, we investigate how Homes' law can be realized together with linear-T resistivity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In this work, we combine the holographic superfluid model of [47] with the holographic solid model of [55] to build a holographic supersolid -a holographic system which breaks spontaneously translations together with a global U (1) symmetry. The combination of superfluidity with broken translations has been already discussed in the holographic literature [68][69][70][71][72][73][74][75][76][77][78][79] but always in the context of momentum dissipation, i.e. explicit breaking of translations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we combine the holographic superfluid model of [47] with the holographic solid model of [55] to build a holographic supersolid -a holographic system which breaks spontaneously translations together with a global U (1) symmetry. The combination of superfluidity with broken translations has been already discussed in the holographic literature [68][69][70][71][72][73][74][75][76][77][78][79] but always in the context of momentum dissipation, i.e. explicit breaking of translations.…”
Section: Introductionmentioning
confidence: 99%
“…The holographic superconductor models with momentum dissipation have also been constructed and studied [42][43][44][45][46][47][48][49]. In Ref.…”
mentioning
confidence: 99%
“…In Ref. [46], a more phenomenologically relevant holographic superconducting model of momentum dissipation was constructed based on Gubser-Rocha model whose ground state entropy vanshes [50]. It was also shown that some universal properties of high T c superconductors, including linear-T resistivity near T c and Homes' law, are observed [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation